Comparative study for adsorption of congo red and methylene blue dye on chitosan modified hybrid nanocomposite. (September 2021) - Ahmad, Rais; Ansari, Khalid
Graphical abstract: Highlights: The hybrid clay with chitosan modified nanocomposite was synthesized. The optimum pH for removal of CR and MB dyes were found to be 6 and 7 respectively. Nanocomposite showed high qm of 104.63 and 99.01 mgg −1 for CR and MB dyes. Langmuir and pseudo-second order model were best fitted for adsorption process. Above 85 % of CR and 88 % of MB dyes could be desorbed in a first cycle. Abstract: The present paper reports the synthesis of an eco-friendly and low-cost chitosan modified hybrid Azadirachta indica leaves powder-Kaolinite clay (Chit/AILP-Kao) nanocomposite and further explored as a potential adsorbent to remove hazardous congo red (CR) and methylene blue (MB) dyes from aqueous solution. The optimum pH for the sequestration of CR and MB dye were found to be 6 and 7 respectively. Among the evaluated isotherms, equilibrium data was found to be the best fitted by Langmuir model on the basis of higher value of coefficient R 2 (0.998). The maximum monolayer adsorption capacity (qm ) for CR and MB dyes were found to be 104.6, 99.01 mgg −1 respectively at optimum pH and temperature 30 °C. To determine the adsorption process kinetic model was best obeyed by pseudo second order on the basis of higher value of coefficient R 2 (0.998). In the thermodynamic parameters, negative values of ΔG° and positive values ΔH o confirms the spontaneous and endothermic nature of adsorption process. The values of maximum specific surface area for CR dye was found to be 210.7 m 2 g -1 while for MB dye it was 223.7 m 2 g -1 . The regeneration study confirmed that the present nanocomposite can be regenerated upto fifth cycle successfully.